Migrant Identity: Maintenance of Lithuanianness, Language Attitudes and Language Policy in Lithuanian Diaspora - Gribauskienė Skirmantė (Darnioji daugiakalbystė)
Ethnic, linguistic identity, heritage language maintenance and transmission, language attitudes and policies remain important topics in nowadays globalized world. The main purpose of this study, which is a part of a large-scale research on Lithuanian heritage language, was to analyze the linguistic and ethnic identity development within Lithuanian diaspora. The article investigates the linguistic attitudes, language practices and language policies within the Lithuanian diaspora in Ireland and Norway, paying extra attention to the younger (K2) generation of Lithuanian migrants. A specialized sociolinguistic questionnaire was developed for this study. A total of 74 first-generation Lithuanian emigrants based in Ireland (n = 18) and Norway (n = 56) participated in the online survey. All participants had children aged 4–17. The data from the questionnaire survey are also illustrated with examples from 5 semi-structured interviews. The study revealed that emigrants from both countries maintain a strong connection with their country of origin. Almost half of the respondents claim that their children visit Lithuania at least once a year, while more than a third of respondents’ children visit Lithuania twice a year or more often. A third of participants are planning to return to Lithuania. Most of the respondents enroll their children to Lithuanian Saturday schools. However, the younger generation seem to differ from their parents in their language attitudes and practices: Lithuanian children based in Ireland tend to feel a stronger connection with the majority language (English) than Lithuanian. Meanwhile, children in Norway are multilinguals, having more than two languages in their everyday repertoire. To summarize, the study demonstrated the main language attitudes and practices of Lithuanians abroad and also highlighted some differences between the first and the second generation of Lithuanian migrants. The results from this study might provide interesting insights for future studies in the fields of sociology, sociolinguistics, and diaspora studies.